Eucalypt Seed for Indian Plantations from better Australian Natural Seed Sources - Boland, D. J. (Indian Forester, 1981)
A summary is presented of the main recommendations from a consultancy visit to India on eucalypt seed supply. The most important suggestion is that seed production areas, particularly Eucalyptus tereticornis and E.camaldulensis should be established in several Indian States as soon as possible from small quantities of seed (approx 1kg per stand) containing a wide genetic base supplied under the Australian Development Assistance Bureau (ADAB) grant to the seed section, Division of Forest Research (DFR) Common wealth Scientific and Industrial Research Organisation (CSIRO). Seed has already been despatched to India for this purpose. The aim is to provide India with some self sufficiency in eucalypt seed requirements of the better Australian natural seed sources so far identified. Suggestions for the establishment of eucalypt seed production areas and on other suitable eucalypt species for planting are indicated. Some thoughts are advanced on the current taxonomic status of Eucalyptus hybrid.